Structural features within the nascent chain regulate alternative targeting of secretory proteins to mitochondria. (12th March 2013) - Pfeiffer, Natalie V; Dirndorfer, Daniela; Lang, Sven; Resenberger, Ulrike K; Restelli, Lisa M; Hemion, Charles; Miesbauer, Margit; Frank, Stephan; Neutzner, Albert; Zimmermann, Richard; Winklhofer, Konstanze F; Tatzelt, Jörg
<x xml:space="preserve">Abstract</x> Protein targeting to specified cellular compartments is essential to maintain cell function and homeostasis. In eukaryotic cells, two major pathways rely on N‐terminal signal peptides to target proteins to either the endoplasmic reticulum (ER) or mitochondria. In this study, we show that the ER signal peptides of the prion protein‐like protein shadoo, the neuropeptide hormone somatostatin and the amyloid precursor protein have the property to mediate alternative targeting to mitochondria. Remarkably, the targeting direction of these signal peptides is determined by structural elements within the nascent chain. Each of the identified signal peptides promotes efficient ER import of nascent chains containing α‐helical domains, but targets unstructured polypeptides to mitochondria. Moreover, we observed that mitochondrial targeting by the ER signal peptides correlates inversely with ER import efficiency. When ER import is compromised, targeting to mitochondria is enhanced, whereas improving ER import efficiency decreases mitochondrial targeting. In conclusion, our study reveals a novel mechanism of dual targeting to either the ER or mitochondria that is mediated by structural features within the nascent chain.